Desenvolvimento socioemocional de crianças em processo de alfabetização: vivências na escola e na família - Paulino, Iêne Kellen (Brasil, 2025)
The general objective of this study was to investigate how socio-emotional skills and competencies are developed in children in the process of learning to read and write. It is important to note that these skills are essential for well-being, academic and personal success, and that school and family are fundamental agents for their full development. The study initially addresses the concepts and benefits of socio-emotional skills in literacy. It then discusses how these skills can be developed in the family and school context. The third part presents proposals for activities that promote socio-emotional development during the literacy process. Finally, an analysis of the data and results is made in light of the dialogue with the theorists studied, followed by the final considerations. The research reinforces the importance of the partnership between family and school to create a welcoming environment that is conducive to the integral development of children. It is concluded that a quality integral education contributes significantly to the formation of emotionally balanced citizens who are prepared for the challenges of everyday life.